Synthesis and characterization of oil palm trunk hemicellulose derivatives for coagulation/flocculation removal of cationic dyes - Shaari, Norsalliana (2016)
Oil palm biomass such oil palm empty fruit bunch, oil palm frond and oil palm trunk (OPT) are considered as the most abundant agrowastes that have the potential to be utilized as raw materials for production of value-added products. Thus, the objective of this study is to synthesize a new novel flocculant based on hemicellulose derived from OPT for cationic dye removal application. Two different flocculants were synthesized in this study: (a) hemicellulose etherified with chloroacetic acid (HcECA) and (b) hemicellulose etherified with acrylamide (HcEAM). Both hemicellulose derivatives were prepared with various etherification mole ratios. The native hemicellulose and its derivatives were characterized using gel permeation chromatography, Fourier transform infrared and proton nuclear magnetic resonance. The coagulation/flocculation performance of the hemicellulose derivatives were evaluated with cationic dye (i.e. methylene blue, MB) at different initial pH values, hemicellulose derivative dosages and initial dye concentrations. The characterization results confirmed a successful synthesis of the respective hemicellulose derivatives with the improvement on the solubility of both derivatives. The coagulation/flocculation results indicated that HcECA15 has better ability to remove the cationic dyes compared to HcECA10 and HcECA5 whereas, HcEAM1 was better than HcEAM0.1, HcEAM0.5, HcEAM10 and HcEAM15. Changing the initial pH of the dye solution from acidic to alkaline resulted in the increase of dye removal percentage. In addition, higher dosages of hemicellulose derivatives also increased dye removal. On the contrary, high initial dye concentrations reduced the percentage of dye removal. HcEAM showed better efficiency on the cationic dye removal than HcECA due to its ability to produce denser flocs which are usually helpful during sedimentation. As a conclusion, both hemicellulose derivatives have their own novelty to be new flocculants for successful application in cationic dye removal processes. Yet, both flocculants had not fully decolourized the MB and still not highly likely to be applied in real industrial applications for textile wastewater treatment. Thus, the process, ratio of the etherification and mechanism of MB removal should be investigated further to enhance the dye removal performance